2022
DOI: 10.1021/acs.jafc.2c03069
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cucumber Green Mottle Mosaic Virus Infection by Boron Application: From the Perspective of Nutrient Elements and Carbohydrates

Abstract: Cucumber green mottle mosaic virus (CGMMV) infection causes “blood flesh” symptoms in watermelon fruits, which severely reduces yield and edibleness. However, the growth of watermelon fruits is strongly associated with boron (B), a trace element for improving fruit quality. In this study, B-gradient hydroponic experiments (B concentration: 0, 2.86, and 5.72 mg·L–1 H3BO3) and foliar-spray experiments (B concentration: 30 and 300 mg·L–1 H3BO3) were performed. We found that the B-supplement could inhibit CGMMV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Our laboratory has reported that leaf spraying with boron or growing in boron nutrient solution can relieve the symptoms of blood flesh disease caused by CGMMV infection in watermelon (Bi et al, 2022a). CGMMV infection affects the metabolism of carbohydrates in watermelon, and exogenous boron induces ClNIP5;1 and ClSWEET4 expression, restores and maintains their homeostasis (Bi et al, 2022a). In addition, boron can also induce watermelon resistance to CGMMV infection by regulating ROSrelated genes, such as ClCat, ClPrx and ClGST (Guo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has reported that leaf spraying with boron or growing in boron nutrient solution can relieve the symptoms of blood flesh disease caused by CGMMV infection in watermelon (Bi et al, 2022a). CGMMV infection affects the metabolism of carbohydrates in watermelon, and exogenous boron induces ClNIP5;1 and ClSWEET4 expression, restores and maintains their homeostasis (Bi et al, 2022a). In addition, boron can also induce watermelon resistance to CGMMV infection by regulating ROSrelated genes, such as ClCat, ClPrx and ClGST (Guo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the roles of trace elements in plant antiviral responses are still limited. Our previous studies have shown that boron can inhibit cucumber green mottle mosaic virus (CGMMV) infection in watermelon by regulating the expression levels of genes related to carbohydrate metabolism, hormone biosynthesis, cell wall catabolism and ROS burst (Bi et al, 2022a;Bi et al, 2022b;Guo et al, 2022). In this study, we demonstrated that foliar spraying of Fe inhibited PVY infection in N. tabacum, and analyzed the expression patterns of tobacco genes under four different treatments with or without PVY infection after spraying Fe or H 2 O at 1, 3, 9 days post inoculation (dpi) by full-length transcriptome and RNA-Seq analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the study on nutrient element-induced resistance to PVY infection in host plants is also conducive to improving crop yield from the perspective of PVY control. Our laboratory has reported that leaf spraying with boron or growing in boron nutrient solution can relieve the symptoms of blood flesh disease caused by CGMMV infection in watermelon ( Bi et al., 2022a ). CGMMV infection affects the metabolism of carbohydrates in watermelon, and exogenous boron induces ClNIP5;1 and ClSWEET4 expression, restores and maintains their homeostasis ( Bi et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has reported that leaf spraying with boron or growing in boron nutrient solution can relieve the symptoms of blood flesh disease caused by CGMMV infection in watermelon ( Bi et al., 2022a ). CGMMV infection affects the metabolism of carbohydrates in watermelon, and exogenous boron induces ClNIP5;1 and ClSWEET4 expression, restores and maintains their homeostasis ( Bi et al., 2022a ). In addition, boron can also induce watermelon resistance to CGMMV infection by regulating ROS-related genes, such as ClCat , ClPrx and ClGST ( Guo et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation